The impact of Angiopoietin-2 genetic polymorphisms on susceptibility for malignant breast neoplasms - Gui-Nv Hu; Yan Wang; Chih-Hsin Tang; Lu-Lu Jin; Bi-Fei Huang; Qian Wang; Jun-Kang Shao; Chao-Qun Wang; Chen-Ming Su (Scientific Reports, 2022)
Abstract Breast cancer causes morbidity and mortality among women worldwide, despite much research illuminating the genetic basis of this disease. Anti-angiogenesis therapies have been widely studied, although the association between angiopoietin-2 (ANGPT2) single nucleotide polymorphisms (SNPs) and breast cancer subtypes remains unclear. This case–control study included 464 patients with malignant breast neoplasms and 539 cancer-free females. We explored the effects of ANGPT2 SNPs on the susceptibility for a malignant breast neoplasm in a Chinese Han population. Five ANGPT2 SNPs (rs2442598, rs734701, rs1823375, 11,137,037, and rs12674822) were analyzed using TaqMan SNP genotyping. Carriers of the variant GG allele of rs1823375 were less likely than wild-type carriers to be diagnosed with clinically staged breast cancer, while females with human epidermal growth factor receptor 2 (HER2)-enriched disease carrying the CG or the CG+GG genotype at rs1823375 were significantly less likely than CC genotype carriers to be of lymph node status N1–N3. We also found that the T-T-C-A-T ANGPT2 haplotype significantly increased the risk for developing a malignant breast neoplasm by 1.385-fold (95% CI: 1.025–1.871; p < 0.05). Our study is the first to document a correlation between ANGPT2 polymorphisms and the development and progression of a malignant breast neoplasm in females of Chinese Han ethnicity.